Neuroethics transformation of economic rationality: implications for decision making in business - Lozano, José-Félix (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
The economy and business field has traditionally been dominated by a conception of calculator, strategic and profit-maximizing individual rationality. This model of rationality has important theoretical limitations and practical consequences. In recent decades the results of neuroethics´ research seems open new ways for understanding the practical rationality. These new routes, representing a revaluation of emotional and intuitive dimension in cognitive ability and have great relevance for business and economic decision making. The aim of this paper is to analyse the implications of a rational dialogic-friendly (cor-cordis) concept for economic and business decision-making. Our work proposes a version of the dialogic-friendly practical rationality that integrate advances in neuroethics with the discursive rationality perspective in order to overcome the strategic rationality and emotivist intuitionism.